Sosialisasi Dampak Penggunaan Gedget Berlebih bagi Otak pada Usia Remaja - Deni Nasir Ahmad; Luluk Setyowati; Westri Andayanti; Mal Alfahnum; Maya Masitha Astriani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The community service team observed that a common issue faced by students in partner schools is difficulty focusing during lessons, largely due to distractions from gadgets, particularly social media. Many students become fixated on social media applications, ignoring ongoing lessons. This concern has prompted our partner schools to organize interactive discussions and provide information on how to use social media wisely and manage time between learning and gadget use. And the goal of our community service was to raise awareness and provide training on responsible social media use, prevent the impact of social media on adolescent brain development (brain rot), and improve students' focus and thinking skills. The methods used in this community service included: (a) analyzing the needs and problems, (b) observing and understanding the policies of the partner schools in addressing these issues, and (c) conducting activities that involved socializing responsible social media use and brain development training. The community service was conducted on Tuesday, June 17, 2025, at MA Bina Mulia, Pasir Putih Village, Sawangan District, Depok, West Java, from 08:00 to 10:00 WIB. The event consisted of a presentation on